Definition of the Immune Parameters Related to COVID-19 Severity - Birindelli, Sarah; Tarkowski, Maciej S.; Gallucci, Marcello; Schiuma, Marco; Covizzi, Alice; Lewkowicz, Przemysław; Aloisio, Elena; Falvella, Felicia Stefania; Dolci, Alberto; Riva, Agostino; Galli, Massimo; Panteghini, Mauro (Frontiers in Immunology, 2022)
A relevant portion of patients with disease caused by the ‘severe acute respiratory syndrome coronavirus 2’ (COVID-19) experience negative outcome and several laboratory tests have been proposed to predict disease severity. Among others, dramatic changes in peripheral blood cells have been described. We developed and validated a laboratory score solely based on blood cell parameters to predict survival in hospitalized COVID-19 patients. We retrospectively analyzed 1619 blood cell counts from 226 consecutively hospitalized COVID-19 patients to select parameters for inclusion in a laboratory score predicting severity of disease and survival. The score was derived from lymphocyte and granulocytes associated parameters and validated on a separate cohort of 140 consecutive COVID-19 patients. Using ROC curve analysis, a best cut-off for score of 30.6 was derived, which was associated to an overall 82.0% sensitivity (95% CI: 78-84) and 82.5% specificity (95% CI: 80-84), respectively, for detecting outcome. The scoring trend effectively separated survivors and non-survivors’ groups, starting two weeks before the end of the hospitalization period. Patients’ score time points were also classified into mild, moderate, severe, and critical according to the symptomatic oxygen-therapy administered. Fluctuations of the score should be recorded to highlight a favorable or unfortunate trend of the disease. The predictive score was found reflecting and anticipating the disease gravity, defined by the type of the oxygen support used, giving a proof of its clinical relevance. It offers a fast and reliable tool for supporting clinical decisions and, most important, triage in terms not only of prioritization but also allocation of limited medical resources, especially in the period when therapies are still symptomatic and many, under development. In fact, a prolonged and progressive increase of the score can suggest impaired chances of survival and/or urgent need to Intensive Care Unit admission.